Photocatalyst film and display device

CN117380288BActive Publication Date: 2026-10-30SHARP KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310813841.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-07-06
Filing Date
2023-07-04
Publication Date
2026-10-30
Estimated Expiration
2043-07-04

AI Technical Summary

Benefits of technology

[0006]由于上述光催化剂涂布层含有光催化剂粒子,因此光催化剂薄膜能够具有优异的光催化活性及抗菌抗病毒活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117380288B_ABST
    Figure CN117380288B_ABST
Patent Text Reader

Abstract

The present invention provides a photocatalyst film having excellent scratch resistance. The photocatalyst film of the present invention includes a base film, a hard coat layer provided on the base film, and a photocatalyst coating layer provided on the hard coat layer, the hard coat layer containing an ultraviolet-cured resin, and the photocatalyst coating layer containing photocatalyst particles and a binder, the photocatalyst particles being tungsten oxide particles, and the binder being a hydrolytic condensate of a tetraalkoxysilane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a photocatalyst thin film and a display device. Background Technology

[0002] The photocatalyst acquires photocatalytic activity by receiving light. This photocatalytic activity can remove harmful substances from the air, such as VOCs (volatile organic compounds), and deactivate allergens (see, for example, Patent Document 1). In this document, a hydrolytic condensate of tetraalkoxysilane is used as the binder for the photocatalyst coating layer. By using such a binder, the oxidative decomposition of the binder due to photocatalytic activity can be suppressed. In addition, there are known optical films that are adhered to displays (see, for example, Patent Document 2). Existing technical documents Patent documents

[0003] Patent Document 1: Japanese Patent Application Publication No. 2011-111600 Patent Document 2: Japanese Patent Application Publication No. 2021-059734 Summary of the Invention The technical problem to be solved by the present invention

[0004] The hydrolysis condensate of tetraalkoxysilane after complete hydrolysis and dehydration condensation is SiO2. Therefore, photocatalyst coatings containing tetraalkoxysilane hydrolysis condensates as binders sometimes exhibit reduced toughness, cracking, and partial peeling. Consequently, photocatalyst coatings are easily damaged. The present invention was made in view of this situation, and provides a photocatalyst film with excellent scratch resistance. Technical solutions for solving technical problems

[0005] This disclosure provides a photocatalyst film, characterized in that it comprises: a base film, a hard coating disposed on the base film, and a photocatalyst coating layer disposed on the hard coating layer, wherein the hard coating layer contains an ultraviolet-curable resin, the photocatalyst coating layer contains photocatalyst particles and a binder, wherein the photocatalyst particles are tungsten oxide particles, and the binder is a hydrolysis condensate of tetraalkoxysilane. Beneficial effects

[0006] Because the above-mentioned photocatalyst coating layer contains photocatalyst particles, the photocatalyst film can have excellent photocatalytic activity and antibacterial and antiviral activity. The binder in the aforementioned photocatalyst coating layer is a hydrolysis condensate of tetraalkoxysilane. This inorganic binder prevents the binder from decomposing due to the photocatalyst's activity. Therefore, the photocatalyst film's scratch resistance and antibacterial and antiviral properties can be maintained for a long time. The photocatalyst film disclosed herein has a hard coating comprising an ultraviolet-curable resin between the substrate film and the photocatalyst coating layer. Therefore, it is possible to suppress the peeling of the photocatalyst coating layer from the photocatalyst film, and in addition, it is possible to suppress partial peeling caused by cracking of the photocatalyst coating layer due to the toughness of the hard coating layer, thereby enabling the photocatalyst film to have excellent scratch resistance. Attached Figure Description

[0007] Figure 1 This is a schematic cross-sectional view of a photocatalyst film according to an embodiment of the present invention. Figure 2 This is a schematic cross-sectional view of a display device according to an embodiment of the present invention. Figure 3 It is the chemical reaction formula for the hydrolysis and condensation reaction of tetraalkoxysilane. Detailed Implementation

[0008] The photocatalyst film disclosed herein comprises: a base film, a hard coating disposed on the base film, and a photocatalyst coating layer disposed on the hard coating layer. The hard coating layer contains an ultraviolet-curable resin, and the photocatalyst coating layer contains photocatalyst particles and a binder. The photocatalyst particles are tungsten oxide particles, and the binder is a hydrolysis condensate of tetraalkoxysilane.

[0009] The hard coating preferably contains a UV-curable resin and inorganic particles, and the weight percentage of the inorganic particles in the hard coating is preferably 5 wt% or more and 50 wt% or less. This increases the hardness of the hard coating and allows the photocatalyst film to have high transparency. The inorganic particles are preferably silicon dioxide particles. This improves the adhesion between the hard coating layer and the photocatalyst coating layer. The average particle size D50 of the inorganic particles is preferably 5 nm or more and 80 nm or less. Therefore, the photocatalyst film can possess excellent transparency. The inorganic particles are preferably at least one of copper compound particles, silver particles, and silver compound particles. This enhances the antiviral activity of the photocatalyst film.

[0010] The UV-curable resin preferably has hydroxyl groups. This improves the adhesion between the hard coating layer and the photocatalyst coating layer. The UV-curable resin preferably contains a polymerization initiator, which is preferably an acylphosphine oxide-based polymerization initiator. If an acylphosphine oxide-based polymerization initiator is used, an acid will be generated as a byproduct when the UV-curable resin begins its curing reaction. This acid improves the curability of the photocatalyst coating layer and enhances the scratch resistance of the photocatalyst film. Furthermore, the acid also improves the antibacterial and antiviral properties of the photocatalyst film. The thickness of the hard coating is preferably 1 μm or more and 10 μm or less. Therefore, the photocatalyst film can exhibit excellent scratch resistance and flexibility, and it can also suppress hard coating cracking and reduce haze.

[0011] The average particle size D50 of the aforementioned photocatalyst particles is preferably 10 nm or more and 5000 nm or less. This helps to suppress the increase in haze of the photocatalyst film. The hydrolysis condensate is preferably a long-chain siloxane compound. This helps to suppress the increase in viscosity of the photocatalytic coating agent used in the fabrication of the photocatalyst coating layer. Therefore, the surface roughness of the formed photocatalyst coating layer can be reduced, and the increase in haze of the photocatalyst film containing the photocatalyst coating layer can be suppressed.

[0012] The photocatalyst coating layer preferably contains a fluoropolymer. This improves the surface smoothness (flowability) of the photocatalyst coating layer, reducing haze even with a high proportion of photocatalyst particles and high antiviral activity. Furthermore, it enhances the abrasion resistance (brush resistance) of the photocatalyst coating layer. The thickness of the photocatalyst coating layer is preferably 0.1 μm or more and 5.0 μm or less. This results in a photocatalyst coating with high photocatalytic activity while suppressing increased haze in the photocatalyst film. The display device disclosed herein includes the photocatalyst thin film disclosed herein.

[0013] Hereinafter, an embodiment of the present invention will be described using the accompanying drawings. The configuration shown in the drawings or the following description is illustrative, and the scope of the present invention is not limited to the contents shown in the drawings or the following description.

[0014] Figure 1 This is a schematic cross-sectional view of the photocatalyst film of this embodiment. Figure 2 This is a schematic cross-sectional view of the display device according to this embodiment. The photocatalyst film 10 of this embodiment includes: a base film 2, a hard coating layer 3 disposed on the base film 2, and a photocatalyst coating layer 4 disposed on the hard coating layer 3. The hard coating layer 3 contains an ultraviolet-curable resin, and the photocatalyst coating layer 4 contains photocatalyst particles and an adhesive. The photocatalyst particles are tungsten oxide particles, and the adhesive is a hydrolysis condensate of tetraalkoxysilane. The photocatalyst film 10 can be used as an antibacterial / antiviral film that can be adhered to a display.

[0015] The display device 12 can be composed of, for example, a liquid crystal display (LCD) or an organic EL display. Alternatively, the display device 12 can also be a touch panel display. Furthermore, the display device 12 can be an operation panel assembled into a multifunction printer, or it can be the display of a smartphone. The display device 12 can be manufactured, for example, by attaching a photocatalyst film 10 to the display section 11.

[0016] The base film 2 is the film that serves as the base film of the photocatalyst film 10. The base film 2 can be, for example, an optical film such as a PET film, a cellulose triacetate film, a cyclic olefin polymer film, or a polyurethane resin film. Alternatively, the base film 2 can also be a light-transmitting resin film.

[0017] The hard coating layer 3 is disposed between the base film 2 and the photocatalyst coating layer 4, and functions to prevent damage to the photocatalyst film 10. The hard coating layer 3 contains a UV-curable resin. Therefore, peeling of the hard coating layer 3 from the base film 2 can be inhibited. The hard coating layer 3 may also be a resin layer. The thickness of the hard coating 3 is 1 μm or more and 10 μm or less, preferably 2 μm or more and 8 μm or less, and more preferably 3 μm or more and 6 μm or less. As a result, the photocatalyst film 10 can have excellent scratch resistance, while also having excellent flexibility. In addition, it can suppress the cracking of the hard coating 3 and reduce haze.

[0018] UV-curable resins are resins that form cross-linked structures through reactions between polymerizable oligomers and monomers such as vinyl, acryloyl, and epoxy groups, using free radicals and cations generated by light (ultraviolet) irradiation as initiators. UV-curable resins can be either free radical polymers or cationic polymers. They may also contain polymerization initiators, such as acylphosphine oxide initiators. When using such an initiator, an acid is generated as a byproduct during the initial curing reaction of the UV-curable resin. This acid improves the curability of the photocatalyst coating layer 4, thus enhancing the scratch resistance of the photocatalyst film 10. Furthermore, the acid also improves the antibacterial / antiviral properties of the photocatalyst film 10.

[0019] The UV-curable resin preferably has hydroxyl groups. This improves the adhesion between the hard coating layer 3 and the photocatalyst coating layer 4. Specifically, the hydroxyl groups generated from the hydrolysis of residual alkoxy groups (-OR) in the hydrolytic condensate (adhesive) contained in the photocatalyst coating layer 4 undergo a dehydration condensation reaction with the hydroxyl groups of the UV-curable resin contained in the hard coating layer 3, thereby enabling chemical bonding between the adhesive and the UV-curable resin. As a result, the photocatalyst film 10 exhibits excellent scratch resistance. The hydroxyl groups in the UV-curable resin are preferably primary hydroxyl groups. Examples of monomers and oligomers containing primary hydroxyl groups include 4-hydroxybutyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 4-hydroxybutyl methacrylate, diethylene glycol methacrylate, and polyethylene glycol methacrylate.

[0020] The hard coating 3 may contain a UV-curable resin and inorganic particles. In this case, the hard coating 3 may have a structure in which inorganic particles are dispersed in the UV-curable resin serving as a matrix. This increases the hardness of the hard coating, thereby improving the scratch resistance of the photocatalyst film 10. The weight percentage of inorganic particles in the hard coating 3 is 5 wt% or more and 50 wt% or less, preferably 10 wt% or more and 45 wt% or less, more preferably 15 wt% or more and 40 wt% or less. This increases the hardness of the hard coating, and the photocatalyst film can have high transparency.

[0021] The inorganic particles contained in the hard coating 3 are, for example, oxide particles, silicon dioxide particles, copper compound particles, silver particles, silver compound particles, etc. Furthermore, the inorganic particles can have an oxide layer on their surface. The inorganic particles are preferably oxide particles such as silica particles or particles with an oxide layer on their surface. This improves the adhesion between the hard coating layer 3 and the photocatalyst coating layer 4. Specifically, by hydrolyzing the residual alkoxy groups (-OR) in the hydrolytic condensate (binder) contained in the photocatalyst coating layer 4 to generate hydroxyl groups, which then undergo a dehydration condensation reaction with the hydroxyl groups on the surface of the inorganic particles on the hard coating layer 3, the binder and the inorganic particles can be chemically bonded. When the inorganic particles are silica particles, the average particle size D50 of the inorganic particles is, for example, 5 nm or more and 80 nm or less, preferably 10 nm or more and 45 nm or less. Therefore, the photocatalyst film 10 can exhibit excellent transparency.

[0022] The inorganic particles contained in the hard coating 3 can be copper compound particles, silver particles, or silver compound particles. This enhances the antiviral activity of the photocatalyst film 10. Furthermore, the hard coating 3 can contain various inorganic particles. For example, the hard coating 3 can contain oxide particles and silver particles.

[0023] The hard coating 3 can be formed, for example, by applying a UV-curable coating to the base film 2 and then curing the coating by irradiating it with ultraviolet light. The application method is not particularly limited; for example, a thin-film coater can be used to apply the UV-curable coating to one side of the base film. UV-curable coatings may contain oligomers, photopolymerization initiators, and solvents. They may also contain monomers, inorganic particles, or be solvent-free.

[0024] Oligomers include, for example, polyester acrylates, polyurethane acrylates, and epoxy acrylates. Monomers include, for example, polyfunctional acrylate monomers and monofunctional acrylate monomers. Photopolymerization initiators include, for example, acylphosphine oxide polymerization initiators, benzophenone polymerization initiators, acetophenone polymerization initiators, benzoin ether polymerization initiators, and thioxanone polymerization initiators. Solvents include, for example, methyl ethyl ketone (MEK).

[0025] A photocatalyst coating layer 4 is disposed on the hard coating layer 3 and contains photocatalyst particles and a binder. The photocatalyst particles are particles that exhibit photocatalytic activity by absorbing light, specifically tungsten oxide particles (WO3 particles). Due to its wide light absorption bandwidth, tungsten oxide exhibits photocatalytic activity by absorbing visible light. Therefore, it can exert photocatalytic activity by absorbing light from displays such as liquid crystal displays, organic EL displays, plasma displays, and micro LED displays, and can oxidize organic substances such as viruses.

[0026] The photocatalyst coating layer 4 is formed by applying a photocatalyst coating agent onto the hard coating layer 3 and then drying the coating. The application method for the photocatalyst coating agent is not particularly limited; for example, coating, spraying, spin coating, or dip coating methods used in film application can be employed. The thickness of the photocatalyst coating layer 4 is 0.1 μm or more and 5.0 μm or less, preferably 0.3 μm or more and 3.0 μm or less, and more preferably 0.5 μm or more and 1.0 μm or less. Therefore, the photocatalyst coating layer 4 can possess high photocatalyst activity while simultaneously suppressing the increase in haze of the photocatalyst film 10.

[0027] Tungsten oxide particles (WO3 particles) used as photocatalyst particles can be tungsten oxide particles with a composition deviating from stoichiometry, provided they possess photocatalytic activity. Furthermore, tungsten oxide particles can contain impurity atoms or added atoms within a range that does not lose photocatalytic activity. Additionally, the surface of the photocatalyst particles can also contain a co-catalyst that reduces the energy gap between the photocatalyst particles, thereby improving responsiveness in the visible light region. Co-catalysts include platinum group metals such as Pt, Pd, Rh, Ru, Os, and Ir.

[0028] The average particle size (median particle size D50, particle size at a cumulative distribution of 50 vol%, or BET particle size) of the tungsten oxide particles is 10 nm or more and 5000 nm or less, preferably 30 nm or more and 1000 nm or less, and more preferably 50 nm or more and 200 nm or less. This suppresses the increase in haze of the photocatalyst film. The average particle size of the photocatalyst can be measured using a BET surface area meter, a laser diffraction particle size analyzer, or a dynamic light scattering particle size analyzer. The proportion of tungsten oxide particles in the photocatalyst coating layer 4 is 25 wt% or more and 55 wt% or less, preferably 35 wt% or more and 52 wt% or less.

[0029] The binder included in the photocatalyst coating layer 4 is a hydrolysis condensate of tetraalkoxysilane. The hydrolysis condensate is preferably a long-chain siloxane compound. Alternatively, the binder is preferably a siloxane compound having a linear moiety. Furthermore, the binder may have a polymeric structure such that a dispersion of 10 wt% of the hydrolysis condensate in ethanol has a viscosity of 2.0 cps or more and 4.0 cps or less at 20°C. This suppresses the decomposition of the binder due to photocatalytic activity and prevents the viscosity of the photocatalytic coating agent used in the fabrication of the photocatalyst coating layer 4 from increasing. Therefore, the surface roughness of the formed photocatalyst coating layer 4 can be reduced, and the haze of the photocatalyst film 10 containing the photocatalyst coating layer 4 can be suppressed.

[0030] Long-chain siloxane compounds are compounds with long chain portions linked by siloxane bonds (e.g., compounds with chains linked by dozens or more siloxane bonds). They can be linear siloxane compounds, branched siloxane compounds, or irregularly chained siloxane compounds. The hydroxyl groups of long-chain siloxane compounds can undergo a dehydration condensation reaction with the hydroxyl groups on the surface of photocatalyst particles. At this point, the long-chain siloxane compounds are chemically bonded to the surface of the photocatalyst particles. Furthermore, if the hard coating 3 has hydroxyl groups, the hydroxyl groups contained in the long-chain siloxane compound can also undergo a dehydration condensation reaction with the hydroxyl groups of the hard coating 3. In this case, the long-chain siloxane compound is chemically bonded to the hard coating 3.

[0031] The liquid medium (solvent or dispersion medium) contained in the photocatalytic coating agent used to form the photocatalytic coating layer 4 preferably contains water. Alternatively, the liquid medium may also be a mixture of water and alcohol (e.g., ethanol). The liquid medium may also be a mixture of liquids (e.g., water and alcohol) contained in a binder-containing mixture and liquids (e.g., water and alcohol) applied during the preparation of the photocatalytic coating agent. The proportion of water in the photocatalytic coating agent is, for example, 20 wt% or more and 60 wt% or less, preferably 35 wt% or more and 55 wt% or less. The proportion of alcohol in the photocatalytic coating agent is, for example, 20 wt% or more and 70 wt% or less, preferably 30 wt% or more and 70 wt% or less, and more preferably 40 wt% or more and 60 wt% or less. This improves the stability of the photocatalytic coating agent.

[0032] In the photocatalytic coating agent, photocatalyst particles (photocatalyst powder) are dispersed in a liquid medium. The proportion of tungsten oxide particles in the photocatalytic coating agent is preferably 0.1 wt% or more and 6.0 wt% or less, more preferably 1 wt% or more and 5.0 wt% or less.

[0033] Tetraalkoxysilane Si(OR)4 has a chemical structure with four alkoxy groups (-OR) bonded to silicon atoms (Si). When Si(OR)4 is mixed with water, it undergoes hydrolysis. The silicon compound generated by this hydrolysis grows three-dimensionally through a dehydration condensation reaction, forming a three-dimensional network of SiO2 (glass). Furthermore, the dehydration condensation reaction occurs simultaneously with the hydrolysis reaction. Additionally, to substantially convert all of Si(OR)4 into SiO2, 2 moles of water (H2O) are required for every 1 mole of Si(OR)4. When the hydrolysis and condensation reactions are carried out in the presence of more than 2 moles of water relative to 1 mole of Si(OR)4, a three-dimensional network of SiO2 (sol or gel) is formed.

[0034] When Si(OR)4 undergoes hydrolysis and condensation reactions in a low-water (H2O) environment (first step), such as Figure 3 As shown in chemical reaction formula (a), a portion of the four alkoxy groups in tetraalkoxysilane undergoes a hydrolysis reaction, whereby the alkoxy groups are replaced by hydroxyl groups. Then, as... Figure 3 As shown in chemical reaction (b), the hydroxyl groups generated through hydrolysis undergo a dehydration condensation reaction, causing the silane compound to polymerize, producing a siloxane compound and water (H2O). This water is used for... Figure 3 The hydrolysis reaction is as shown in chemical reaction formula (a). The siloxane compound grows elongatedly by repeatedly performing hydrolysis and dehydration condensation reactions in a chain. This growth of the siloxane compound continues until the water is exhausted (the first hydrolysis condensation reaction). The time for the first hydrolysis condensation reaction (the time for maintaining the temperature and continuous stirring) can be, for example, more than 2 hours and less than 15 hours.

[0035] In the first hydrolysis-condensation reaction (first step), Si(OR)4, an alcohol (e.g., ethanol), and water can be mixed to carry out the hydrolysis and dehydration-condensation reactions. This suppresses the separation of Si(OR)4 from water and allows the hydrolysis and dehydration-condensation reactions to proceed uniformly. In the first hydrolysis-condensation reaction, Si(OR)4, alcohol, water, and an acid catalyst (e.g., hydrochloric acid) can be mixed to carry out both hydrolysis and dehydration-condensation reactions. Thus, the first hydrolysis-condensation reaction can proceed at an appropriate reaction rate. In the first hydrolysis-condensation reaction (first step), the hydrolysis and dehydration-condensation reactions can be carried out at a temperature above the freezing point and below 20°C. This suppresses the increase in branching into the siloxane compound and inhibits the increase in viscosity of the mixture.

[0036] In the first hydrolysis-condensation reaction (first step), the mixing ratio of Si(OR)4 to water can be set to a ratio of water to 1 mole of Si(OR)4 that is 0.5 mol or more and 1 mol or less, preferably 0.6 mol or more and 0.9 mol or less, and even more preferably 0.7 mol or more and 0.8 mol or less. This allows the siloxane compound to grow elongated and forms long-chain siloxane compounds. Furthermore, it suppresses the three-dimensional growth of the siloxane compound and prevents the viscosity of the mixture from increasing.

[0037] After the first hydrolysis-condensation reaction is carried out until the water is substantially depleted, water and an acid catalyst are added to the resulting mixture to allow for further hydrolysis and dehydration-condensation reactions (second step, second hydrolysis-condensation reaction). By completing the second hydrolysis-condensation reaction, a binder (a hydrolysis-condensation compound of Si(OR)4) is synthesized. This binder is a long-chain siloxane compound. In the second hydrolysis-condensation reaction, since the hydrolysis-condensation reaction also occurs with less water (H2O) relative to the alkoxy group (-OR) of the siloxane compound, the siloxane compound grows in a long and thin manner. This growth of the siloxane compound continues until the water is exhausted. The time for carrying out the second hydrolysis-condensation reaction (the time during which the temperature is maintained and stirring is continuous) can, for example, be more than 2 hours and less than 30 hours. In the second hydrolysis-condensation reaction, the amount of water added relative to 1 mole of Si(OR)4 as the starting material can be more than 0.5 moles and less than 1.4 moles. This allows the siloxane compound to grow in a slender form, and the hydrolysis-condensation compound (binder) of Si(OR)4 to become a long chain.

[0038] In the second hydrolysis-condensation reaction (second step), it is preferable that the amount of acid catalyst (e.g., hydrochloric acid) added to the mixture is greater than the amount of acid catalyst mixed in the first hydrolysis-condensation reaction (first step). This allows the molecular weight of the siloxane compound to be increased through the second hydrolysis-condensation reaction, thereby improving the abrasion resistance (brush resistance) of the photocatalyst coating layer 4.

[0039] The total amount of water added in the first hydrolysis-condensation reaction (first step) and the second hydrolysis-condensation reaction (second step) can be more than 1.6 moles and less than 1.9 moles of Si(OR)4. Therefore, the hydrolysis-condensate (binder) of Si(OR)4 after the reaction can have residual alkoxy groups (-OR). When preparing a photocatalytic coating agent by mixing the binder, photocatalyst particles, and water, the hydroxyl groups generated from the hydrolysis of the residual alkoxy groups in the photocatalytic coating agent undergo a dehydration-condensation reaction with the hydroxyl groups on the surface of the photocatalyst particles, thereby chemically bonding the binder to the photocatalyst particles. Therefore, the photocatalyst particles can be firmly fixed using the binder. A photocatalytic coating agent can be prepared by mixing a binder-containing mixture obtained through first and second hydrolysis-condensation reactions (first and second steps) with photocatalyst particles.

[0040] The content of the binder (hydrolysis condensate of Si(OR)4) in the photocatalytic coating agent, calculated based on the SiO2 conversion amount (the amount of SiO2 contained in the photocatalytic coating agent when all Si(OR)4 is converted to SiO2 through hydrolysis condensation reaction), can be 3 wt% or more and 5 wt% or less. The proportion of the binder (hydrolysis condensate of Si(OR)4) in the photocatalytic coating layer 4 formed by drying the photocatalytic coating agent, calculated based on the SiO2 conversion amount (the amount of SiO2 contained in the photocatalytic coating agent when all Si(OR)4 is converted to SiO2 through hydrolysis condensation reaction), is 30 wt% or more and 55 wt% or less, preferably 35 wt% or more and 50 wt% or less.

[0041] The photocatalytic coating agent and the photocatalyst coating layer 4 may contain fluoropolymers. This improves the surface slippage (flowability) of the photocatalyst coating layer 4, reducing haze even with a high proportion of photocatalyst particles and high antiviral activity. Furthermore, it improves the scratch resistance (brush resistance) of the photocatalyst coating layer 4. Examples of fluoropolymers include PTFE, FEP, PFA, PVDF, ETFE, PCTFE, and ECTFE. The proportion of fluoropolymer in the photocatalytic coating agent is 0.5 wt% or more and 5 wt% or less, preferably 1 wt% or more and 4.5 wt% or less. The proportion of fluoropolymer in the photocatalyst coating layer 4 is, for example, 10 wt% or more and 40 wt% or less, preferably 15 wt% or more and 35 wt% or less, and more preferably 20 wt% or more and 30 wt% or less. As fluoropolymers, for example, ZEFFLE S-520, SE-300A, SE-405, SE-600, and SE-700 manufactured by Daikin Industries, Ltd., LUMIFLON FE4300, FE4400, and FE4500 manufactured by AGC Corporation, and SIFCLER F101, F102, and F104 manufactured by E-TEC Corporation can be used.

[0042] The photocatalytic coating agent and the photocatalyst coating layer 4 may contain inorganic particles. Examples of inorganic particles include zirconium oxide particles, copper compound particles, silica particles, silver particles, and silver compound particles. This improves the stability of the photocatalytic coating agent. The reason for this is not yet clear, but it is believed that the zeta potential of these particles is opposite to that of tungsten oxide particles. The proportion of inorganic particles in the photocatalytic coating agent is, for example, 0.01 wt% or more and 0.1 wt% or less. The proportion of inorganic particles in the photocatalyst coating layer 4 is, for example, 0.1 wt% or more and 1.0 wt% or less.

[0043] The photocatalytic coating agent and the photocatalyst coating layer 4 may contain cyclodextrin inclusion complexes. This improves the stability of the photocatalytic coating agent. The reason for this is not yet clear, but it is believed that the inclusion complexes absorb impurities in the photocatalyst coating solution. The proportion of cyclodextrin inclusion complexes in the photocatalytic coating agent is, for example, 0.01 wt% or more and 0.1 wt% or less. The proportion of cyclodextrin inclusion complexes in the photocatalyst coating layer 4 is, for example, 0.1 wt% or more and 1.0 wt% or less.

[0044] Preparation of tungsten oxide particle dispersion Tungsten oxide (WO3) powder (manufactured by KISHIDA Chemical Co., Ltd.) and ion-exchanged water were wet-milled using a bead mill (speed: 10 m / s, processing time: 360 min) to obtain a tungsten oxide dispersion (WO3: 20 wt%). The primary particle size of the tungsten oxide particles was approximately 50 nm. To obtain 0.02 wt% Pt-WO3, hexachloroplatinum(VI) hexahydrate (manufactured by KISHIDA Chemical Co., Ltd.) was added to the tungsten oxide dispersion and dissolved, thereby supporting Pt as a co-catalyst on the surface of the tungsten oxide particles.

[0045] Synthesis of TEOS hydrolysis condensate The hydrolytic condensate PS1 and PS2 were synthesized by hydrolyzing and condensing tetraethoxysilane (TEOS) (ethyl silicate 28, manufactured by COLCOAT Co., Ltd.). In the synthesis of PS1, firstly, the materials for the first hydrolysis-condensation reaction shown in Table 1 were added to a 500 ml flask equipped with a stirrer. The mixture was cooled to a liquid temperature of 10°C, stirred at 100 RPM, and subjected to hydrolysis and condensation reactions for 10 hours. Next, the materials for the second hydrolysis-condensation reaction shown in Table 1 were added to the flask, the mixture was cooled to a liquid temperature of 10°C, stirred at 100 RPM, and subjected to hydrolysis and condensation reactions for 10 hours. In the synthesis of the hydrolysis-condensate PS2, the materials for the second hydrolysis-condensation reaction were not added, and the hydrolysis and condensation reactions were carried out for 20 hours. Furthermore, PS2 was synthesized in the same manner as the hydrolysis-condensate PS1. In addition, Table 1 shows the proportions of the hydrolysis condensate compositions. The proportions of TEOS are converted to the amount of SiO2 (the amount after the hydrolysis and condensation reactions, in which all TEOS is converted to SiO2).

[0046] [Table 1]

[0047] Viscosity Measurement 1 The viscosities of the hydrolysate condensates PS1 and PS2 were measured using a viscometer (VISCOMATE MODEL VM-10A, manufactured by SEKONIC Co., Ltd.). Table 1 shows the measurement results. The viscosity of the hydrolysate PS1 was 2.5 cps, while the viscosity of the hydrolysate PS2 was 5.6 cps. In the hydrolysis condensate PS2, since the molar ratio of water to TEOS in the first hydrolysis condensation reaction is relatively large (1.73), it is assumed that the siloxane compound undergoes three-dimensional growth. Therefore, the viscosity of the hydrolysis condensate PS2 is considered to increase. In the hydrolysis condensate PS1, it is believed that the molar ratio of water to TEOS in the first hydrolysis condensation reaction is small, at 0.75, and the siloxane compound grows in a slender manner. Therefore, it is believed that the viscosity of the hydrolysis condensate PS1 decreases.

[0048] Modulation of photocatalytic coating agent Photocatalytic coating agents LC1, LC2, and LC3 were prepared. Specifically, the substances listed in Table 2, including tungsten oxide dispersion (WO3: 20 wt%), TEOS hydrolysis condensate PS1, lubricant (ZEFFLE S-520, manufactured by Daikin Industries, Ltd., fluoropolymer: 50 wt%), distilled water, and ethanol (manufactured by KISHIDA Chemical Co., Ltd.), were mixed and stirred at the proportions shown in Table 2 to prepare coating agents LC1, LC2, and LC3. Table 2 shows the solid component concentration, proportion, and solid component proportion of the coating agents (in parentheses). The proportions of the hydrolysis condensate in Table 2 are converted to SiO2 (the amount after hydrolysis and condensation reactions, where all TEOS is converted to SiO2). Photocatalytic coating agent LC3 does not contain the TEOS hydrolysis condensate.

[0049] [Table 2]

[0050] Viscosity Measurement 2 The viscosities of photocatalytic coating agents LC1, LC2, and LC3 were measured immediately after preparation using a viscometer (VISCOMATE MODEL VM-10A manufactured by SEKONIC Co., Ltd.). Furthermore, after placing the prepared photocatalytic coating agents at 45°C for 7 days, the viscosities of LC1, LC2, and LC3 were measured again. Based on these measurements, the coating stability (viscosity stability) of the photocatalytic coating agents was evaluated. The measurement and evaluation results are shown in Table 2. In Table 2, ○ indicates coating agents with a viscosity change of less than 3 cps before and after placement. No coating agents showed a viscosity change of more than 3 cps.

[0051] Preparation of UV-curable coatings Modulated UV-curable coatings Specifically, UV-curable coatings HC1 to HC12 are prepared by mixing and stirring the following substances: methyl ethyl ketone (MEK, manufactured by KISHIDA Chemical Co., Ltd.) as a solvent, monomers, oligomers, polymerization initiators, and inorganic microparticles, as shown in Table 3, in the proportions listed in Table 3. Table 3 also shows the total proportions of components other than the solvent and the proportions of components other than the solvent.

[0052] As monomers and oligomers, trimethylolpropane triacrylate (Miramer M300, manufactured by Miwon Specialty Chemical Co., Ltd.), dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer (UA-510H, manufactured by Kyoeisha Chemical Co., Ltd.), polyethylene glycol (200) diacrylate (Miramer M282, manufactured by Miwon Specialty Chemical Co., Ltd.), or 4-hydroxybutyl acrylate (4HBA, manufactured by Osaka Organic Chemical Industry Co., Ltd.) were used. Furthermore, 4-hydroxybutyl acrylate contains hydroxyl groups. In addition, 1-hydroxycyclohexyl-phenyl ketone (Omnirad 184, manufactured by IGM Resins BV) or bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (Omnirad 819, manufactured by IGM Resins BV) were used as polymerization initiators. In addition, as inorganic microparticles, silica sol MEK solvent (MEK-ST-40, manufactured by Nissan Chemical Co., Ltd., particle size: 12 nm), silica sol MEK solvent (MEK-ST-L, manufactured by Nissan Chemical Co., Ltd., particle size: 45 nm), silica sol MEK solvent (MEK-ST-ZL, manufactured by Nissan Chemical Co., Ltd., particle size: 80 nm), copper iodide (I) (manufactured by Tokyo Chemical Industry Co., Ltd.), or silver-based microparticle aqueous dispersion (NOVARON AGT330F, manufactured by Toa Synthetic Co., Ltd.) were used. Furthermore, NOVARON AGT330F was used at a concentration of 40% by replacing water in the solvent with methyl ethyl ketone.

[0053] [Table 3]

[0054] Fabrication of photocatalyst thin films The prepared UV-curable coating was applied to one side of a 100μm thick PET film (COSMOSHINE 100A4360, Toyobo Co., Ltd.) using a film coater (manufactured by OSG SYSTEM Products Co., Ltd.), and the coating layer was dried at 80°C for 1 minute. The dried coating layer was then irradiated with ultraviolet light (250mJ / cm²). 2 The polymerization reaction is carried out to form a hard coating layer that has been cured. In addition, the thickness of the hard coating layer can be adjusted to 1.5μm, 3.5μm or 6.5μm by using a thin film coater with different gap intervals.

[0055] Next, the prepared photocatalytic coating agent was applied to the hard coating layer using a thin film coater, and the coating layer was dried at 80°C for 10 seconds to form a photocatalytic coating layer. Afterward, the PET film, hard coating layer, and photocatalytic coating layer were left at room temperature for one week. Thus, a photocatalytic film comprising a PET film, a hard coating layer, and a photocatalytic coating layer was fabricated (Examples 1-13, Comparative Example 2). The thickness of the photocatalytic coating layer was 0.15 μm, 0.7 μm, or 3.0 μm by using thin film coaters with different gap intervals. Table 4 shows the composition of the fabricated photocatalytic film, the UV-curable coating used in its fabrication, and the photocatalytic coating agent used in its fabrication. The photocatalytic coating layer of the photocatalytic film in Comparative Example 2 did not contain TEOS hydrolysis condensate.

[0056] Table 4 also shows a PET film of a reference example without a hard coating and a photocatalyst coating layer, and a photocatalyst film of Comparative Example 1 without a hard coating. The photocatalyst film of Comparative Example 1 was formed by coating a photocatalytic coating agent onto one side of a PET film and drying the coating at 80°C for 10 seconds. Then, the PET film and the photocatalyst coating layer were left at room temperature for one week. Thus, the photocatalyst film of the comparative example was produced.

[0057] [Table 4]

[0058] Haze measurement The haze (Z / %) of the photocatalyst films of Examples 1-13, Comparative Examples 1 and 2, and the PET film of the Reference Example was measured using a haze meter "NDH7000" manufactured by Nippon Denshoku Kogyo Co., Ltd. Haze is a value calculated based on the ratio of diffused transmitted light to total transmitted light and is affected by the surface roughness of the film. In addition, the higher the haze, the more turbid the film becomes, and the lower its transparency. Table 4 shows the measurement results. In Table 4, films indicated by "◎" have a haze Z of 2 or less, films indicated by "○" have a haze Z greater than 2 and less than 3, and films indicated by "△" have a haze Z greater than 3 and less than 4. There are no films with a haze greater than 4. Here, the cases evaluated as "◎", "○", or "△" are judged as acceptable levels (excellent film transparency).

[0059] Hardness measurement of photocatalyst films Following the method described in JIS K 5600-5-4:1999 (ISO / DIS 15184:1996), a pencil of known hardness was pressed onto the photocatalyst coating layer of the photocatalyst films in Examples 1-13 and Comparative Examples 1 and 2, and the hardness (pencil hardness) of the photocatalyst films was measured (load: 750g). In the reference examples, the hardness was measured by pressing a pencil onto a PET film. Table 4 shows the measurement results. The hardness of the PET film in the reference example is "B", and the hardness of the photocatalyst films in Comparative Examples 1 and 2 is "HB". Therefore, it can be seen that by forming a photocatalyst coating layer on the PET film, the film hardness increases. Furthermore, the photocatalyst films of Examples 1-13, which have a laminated structure of a hard coating layer and a photocatalyst coating layer on the PET film, have a hardness of "2H" or "3H". Therefore, it can be seen that by forming a laminated structure of a hard coating layer and a photocatalyst coating layer on the PET film, the hardness of the photocatalyst film further increases. Additionally, it can be seen that because the photocatalyst coating layer contains a TEOS hydrolysis condensate, the hardness of the photocatalyst film increases.

[0060] Brush resistance test (abrasion resistance test) Using a surface measuring instrument HEIDON-14FW (manufactured by Shin-To Science Co., Ltd.), a load of 500g was applied to the surface of the photocatalyst coating layer of the photocatalyst film of Examples 1-13, Comparative Examples 1 and 2, or the surface of the PET film of the reference example, and rubbed with steel wool #0000 (manufactured by Japan Steel Wool Co., Ltd.) (stroke width: 30mm, speed 100mm / s, number of rubs: 10). The number of surface scratches N was counted by visually observing the photocatalyst films of Examples 1-13, Comparative Examples 1 and 2, and the PET film of the reference example under an illumination of 100 lx (fluorescent lamp). Table 4 shows the measurement results. In Table 4, “◎” indicates a film with 0 scratches N, “O” indicates a film with 1 or more but less than 3 scratches N, “△” indicates a film with 4 or more but less than 10 scratches N, and “×” indicates a film with 11 or more scratches N.

[0061] The scratch resistance of the PET film in the reference example and the photocatalyst films in Comparative Examples 1 and 2 was rated as "×". Furthermore, the scratch resistance of the photocatalyst films in Examples 1-13, which have a hard coating, was rated as "◎" or "〇". Therefore, it can be seen that by providing a hard coating, the scratch resistance of the photocatalyst film can be improved. Additionally, it is known that the photocatalyst coating layer contains a TEOS hydrolysis condensate, which further improves the scratch resistance of the photocatalyst film. Here, the ratings of "◎", "○" or "△" are considered acceptable (excellent scratch resistance).

[0062] tightness A checkerboard peel test (100 squares) as described in JIS-K-5600 was performed to evaluate the adhesion between the base film (PET film) and the hard coating layer, or the adhesion between the hard coating layer and the photocatalyst coating layer. Specifically, a grid pattern (100 squares) was cut into the photocatalyst coating layer and the hard coating layer. Transparent tape was adhered to the photocatalyst coating layer with the cuts made, and then the tape was peeled off. The peeling status of the photocatalyst coating layer on the base film was visually observed, and the number of squares remaining without peeling, "M", was counted. Table 4 shows the measurement results. In Table 4, “◎” indicates a photocatalyst film with 100 residual squares M, “○” indicates a photocatalyst film with 95 to 99 residual squares M, “△” indicates a photocatalyst film with 54 to 80 residual squares M, and “×” indicates a photocatalyst film with 0 to 79 residual squares M. Here, the cases rated as "◎", "○" or "△" are judged as the acceptable level (excellent fit). The adhesion of the photocatalyst film in Comparative Example 2 was rated as "×". Furthermore, the adhesion of the photocatalyst films in Examples 1-13 and Comparative Example 1 was rated as "◎", "〇", or "△", indicating an acceptable level. Therefore, it can be concluded that the photocatalyst coating layer contains a TEOS hydrolysis condensate, thereby improving the adhesion of the photocatalyst film.

[0063] Antiviral test The antiviral activity values ​​of the photocatalyst films of Examples 1-13, Comparative Examples 1 and 2, or PET films of the reference examples were measured according to the method of JIS R1756:2020. Table 4 shows the measurement results. In the evaluation of antiviral activity in Table 4, “○” indicates membranes with an antiviral activity value of 3 or higher, “△” indicates membranes with an antiviral activity value of 2 or higher but less than 3, and “×” indicates membranes with an antiviral activity value of less than 2. Here, a rating of "○" or "△" is considered an acceptable level (excellent antiviral properties). The antiviral properties of the photocatalyst films in Examples 1 to 13 and Comparative Examples 1 and 2 were evaluated as "0" or "△", both of which are acceptable levels.

[0064] Overall evaluation Table 4 also shows the comprehensive evaluation. Among the multiple evaluations shown in Table 4, the comprehensive evaluation of a membrane is set to "×" even if it has only one "×" rating, and the comprehensive evaluation of a membrane without any "×" rating is set to "〇". Explanation of reference numerals in the attached figures

[0065] 2: Base film; 3: Hard coating layer; 4: Photocatalyst coating layer; 10: Photocatalyst thin film; 11: Display section; 12: Display device.

Claims

1. A photocatalyst thin film, characterized in that, The photocatalyst film includes: a base film, a hard coating layer disposed on the base film, and a photocatalyst coating layer disposed on the hard coating layer. The hard coating comprises a UV-curable resin. The photocatalyst coating contains photocatalyst particles, a binder, and a fluoropolymer. The photocatalyst particles are tungsten oxide particles. The adhesive is a hydrolytic condensate of tetraalkoxysilane. The hydrolysis condensate is a long-chain siloxane compound. The UV-curable resin has hydroxyl groups, and the hydroxyl groups generated by the hydrolysis of the hydrolysis condensate undergo a dehydration condensation reaction with the hydroxyl groups of the UV-curable resin to chemically bond the adhesive to the UV-curable resin.

2. The photocatalyst thin film according to claim 1, characterized in that, The hard coating also contains inorganic particles. The inorganic particles in the hard coating have a weight ratio of 5 wt% or more and 50 wt% or less.

3. The photocatalyst thin film according to claim 2, characterized in that, The inorganic particles are silicon dioxide particles.

4. The photocatalyst thin film according to claim 3, characterized in that, The average particle size D50 of the inorganic particles is greater than 5 nm and less than 80 nm.

5. The photocatalyst thin film according to claim 2, characterized in that, The inorganic particles are at least one of copper compound particles, silver particles, and silver compound particles.

6. The photocatalyst thin film according to claim 1, characterized in that, The UV-curable resin contains a polymerization initiator. The polymerization initiator is an acylphosphine oxide-based polymerization initiator.

7. The photocatalyst thin film according to claim 1, characterized in that, The thickness of the hard coating is greater than 1 μm and less than 10 μm.

8. The photocatalyst thin film according to claim 1, characterized in that, The average particle size D50 of the photocatalyst particles is greater than 10 nm and less than 5000 nm.

9. The photocatalyst thin film according to any one of claims 1 to 8, characterized in that, The thickness of the photocatalyst coating is greater than 0.1 μm and less than 5.0 μm.

10. A display device, characterized in that, The display device includes the photocatalyst film as described in claim 1.

Citation Information

Patent Citations

  • Visible light-responsive photocatalyst coating material, coated article and method for inactivating allergen

    JP2011111600A

  • Optical film with adhesive

    JP2021059734A

  • Shatterproofing member with hardenable pressure-sensitive adhesive layer

    CN103547645A

  • Ultraviolet absorbing hardcoat

    CN109689800A

  • Photocatalyst coating liquid and photocatalyst coating film

    JP1999347418A